Rancang bangun sistem monitoring perangkat elektronik berbasis android - Vira Afifah; Muhammad Diono (ABEC Indonesia, 2021)
The development of the technology industry is currently very fast, not to mention that household electrical products are also increasingly varied. All of this equipment really requires electrical energy to operate it. Sometimes in a household there are a lot of electrical appliances, regardless of how much electricity is installed. Safety and comfort problems caused by overload currents are one of the most important things for electric power users. From the description above, the authors found an idea to make equipment that functions to monitor and control the use of electric power, namely a monitoring system and control of electronic devices based on android. The tool uses an ESP32 wifi module, ACS712 current sensor, 4 channel relay and an Android Smartphone. The way this tool works is the ESP32 wifi module measures the incoming current through the ACS712 sensor, after the current is obtained the ESP32 wifi module calculates the electricity usage rate (Tariff = (Power x electricity rate / watt) which is then stored to the server. If an electronic device crosses the power limit, then the electronic device is cut off via a relay on the last device. The server will be given a storage memory of the monitoring results in the form of a graph, so that it can be viewed again and given a scheduling system for the on or off time of each electronic device. On this tool, the accuracy level of the ACS712 current sensor is obtained , at sensor 1 is  98.56%, sensor 2 is 98.54% and sensor 3 is 98.33%.